JURIDICAL ANALYSIS OF CRIMINAL ACTS OF Smuggling USED CLOTHES IN BATAM CITY (Research Study at the Batam Customs Commission) - Anshelyca, Winda (RADJA PUBLIKA, 2022)
The smuggling of used clothes is an act that violates the provisions of the law, the increase in smuggling cases, especially the smuggling of imports of used clothes (secondhand) has caused various impacts, especially the decline in the competitiveness of domestic production. The problem that will be researched and analyzed is how the legal arrangements, implementation, and what factors are obstacles to the criminal act of smuggling used clothes to minimize the number of crimes. Methods of data collection in this research using library research and field studies. Data analysis used qualitative analysis. This type of research uses normative law research and is supported by empirical law research. The results of this legal research reveal that the prevention of criminal acts of smuggling used clothes stipulates that the legal rules related to smuggling are regulated in Law Number 10 of 1995 concerning Customs as amended to Law Number 17 of 2006, as well as making Regulation of the Minister of Trade Number 18 of 2021 Concerning Export Prohibited Goods and Prohibited Import Goods. Customs and Excise is only the implementer of the existing rules in this case the smuggling of used clothes. The obstacles experienced by Customs and Excise in tackling the crime of smuggling used clothes are the resistance or resistance of the smugglers by mobilizing the masses, both on land and at sea. It is hoped that a statutory regulation will be established that provides more specific provisions regarding the prosecution and punishment of used clothing smuggling which emphasizes not only smugglers but also actors who play a direct role in importing used clothing. And it is hoped that strict sanctions behind complete legal regulations related to the criminal act of smuggling used clothes, then all elements related to the legal system are able to understand that the legal rules are made to protect the public from the threat of the dangers of second-hand clothes.